2000
DOI: 10.1063/1.481778
|View full text |Cite
|
Sign up to set email alerts
|

Dipole moment surfaces and the mid- and far-IR spectra of N2-Ar

Abstract: An improved theoretical long-range dispersion plus induction dipole moment surface for N 2-Ar is presented, and detailed numerical simulations are used to test its predictions against experimental far-IR and mid-IR spectra using two previously-reported potential energy surfaces. As was found in earlier work on the mid-IR spectrum using a pure induction dipole surface, the MMSV mod potential of Jäger et al. ͓J. Chem. Soc. Faraday Discuss. 97, 105 ͑1994͔͒ yields distinctly better agreement with both experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…10 The nitrogen diatomic molecule (N 2 ) does not possess a permanent dipole moment, so that the IR active spectral transitions of the complex are produced due to small induction and dispersion effects of the Ar atom interacting with the N 2 diatom. 10 Another CMS leading innovation case is the decade long theory guided (synchrotron sourced) spectroscopic study of ferrocene (Fc). [27][28][29][30][31][32][33][34][35][36][37] The theoretical IR spectral discovery of the more stable Fc eclipsed conformer (D 5h ) 27 shed a light on Fc studies, led and suggested several new measurements of Fc and its derivatives.…”
Section: Microwave and Infrared Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…10 The nitrogen diatomic molecule (N 2 ) does not possess a permanent dipole moment, so that the IR active spectral transitions of the complex are produced due to small induction and dispersion effects of the Ar atom interacting with the N 2 diatom. 10 Another CMS leading innovation case is the decade long theory guided (synchrotron sourced) spectroscopic study of ferrocene (Fc). [27][28][29][30][31][32][33][34][35][36][37] The theoretical IR spectral discovery of the more stable Fc eclipsed conformer (D 5h ) 27 shed a light on Fc studies, led and suggested several new measurements of Fc and its derivatives.…”
Section: Microwave and Infrared Spectroscopymentioning
confidence: 99%
“…2, 9 and the theoretically developed dipole moment function of the VdW complex. 10 The nitrogen diatomic molecule (N 2 ) does not possess a permanent dipole moment, so that the IR active spectral transitions of the complex are produced due to small induction and dispersion effects of the Ar atom interacting with the N 2 diatom. 10 Another CMS leading innovation case is the decade long theory guided (synchrotron sourced) spectroscopic study of ferrocene (Fc).…”
Section: Microwave and Infrared Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The present contribution examines the case of an N 2 molecule interacting with small Ar clusters, surfaces or embedded into an Ar matrix. Because of its importance for atmospheric and planetary processes [21,22], the Ar-N 2 cluster has been widely studied both theoretically [23][24][25][26][27][28][29][30][31][32][33][34][35] and experimentally [36][37][38][39]. These studies have provided an accurate characterization of this complex, of its potential energy surface and of its vibrational and rotational spectra.…”
Section: Introductionmentioning
confidence: 99%
“…The present contribution examines the case of an N 2 molecule interacting with small Ar clusters, surfaces or embedded into an Ar matrix. Because of its importance for atmospheric and planetary processes, , the Ar–N 2 cluster has been widely studied both theoretically and experimentally. These studies have provided an accurate characterization of this complex, of its potential energy surface and of its vibrational and rotational spectra. In particular, they established the existence of two minima of Ar–N 2 : a linear structure and a T-shaped structure, located in shallow potential wells (a few tens of cm –1 ).…”
Section: Introductionmentioning
confidence: 99%